The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1021/ac0487810
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for the Isolation, Derivatization, Chromatographic Separation, and Detection of Carnitine and Acylcarnitines

Abstract: A strategy for detection of carnitine and acylcarnitines is introduced. This versatile system has four components: (1) isolation by protein precipitation/desalting and cation-exchange solid-phase extraction, (2) derivatization of carnitine and acylcarnitines with pentafluorophenacyl trifluoromethanesulfonate, (3) sequential ion-exchange/reversed-phase chromatography using a single non-end-capped C8 column, and (4) detection of carnitine and acylcarnitine pentafluorophenacyl esters using an ion trap mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…This quarternary ammonium compound can be endogenously formed and is required for transport of long-chain fatty acids across intracellular membranes, which is facilitated by oxidation of the fatty acids into acylcarnitines (Strijbis et al, 2010). The suggestion of Met17 being a carnitine conjugate of bendamustine is supported by the most abundant product ion at m/z 424.1624, because the loss of 59.0729 Da (loss of trimethylamine) is characteristic for carnitine and acylcarnitine conjugates (Minkler et al, 2005). Although the mass spectra give no definite answer on the site of the conjugation, it is hypothesized that Met17 may be monohydrolyzed bendamustine, conjugated with carnitine at the butyric acid moiety to form an acylcarnitine derivative.…”
Section: Metabolite Profiling Of Bendamustine In Human Urinementioning
confidence: 99%
“…This quarternary ammonium compound can be endogenously formed and is required for transport of long-chain fatty acids across intracellular membranes, which is facilitated by oxidation of the fatty acids into acylcarnitines (Strijbis et al, 2010). The suggestion of Met17 being a carnitine conjugate of bendamustine is supported by the most abundant product ion at m/z 424.1624, because the loss of 59.0729 Da (loss of trimethylamine) is characteristic for carnitine and acylcarnitine conjugates (Minkler et al, 2005). Although the mass spectra give no definite answer on the site of the conjugation, it is hypothesized that Met17 may be monohydrolyzed bendamustine, conjugated with carnitine at the butyric acid moiety to form an acylcarnitine derivative.…”
Section: Metabolite Profiling Of Bendamustine In Human Urinementioning
confidence: 99%
“…Recovery of acyl-coenzyme A esters from tissue specimens is often disappointing, with documented recoveries between 30 and 60% [1,5,6]. A general procedure for the isolation of a wide range of acyl-coenzyme A esters, with good documented recoveries from tissues, is presently unavailable.Despite their widely different polarities, we have shown that acylcarnitines (short-, medium-, and long-chain) can be isolated, in a single fraction, from biological samples using organic solvent extraction followed by ion-exchange solid phase extraction (SPE) [7]. This is a highly selective approach, since it combines two orthogonal procedures [8] of isolation: organic solvent extraction and ion-exchange.…”
mentioning
confidence: 99%
“…Despite their widely different polarities, we have shown that acylcarnitines (short-, medium-, and long-chain) can be isolated, in a single fraction, from biological samples using organic solvent extraction followed by ion-exchange solid phase extraction (SPE) [7]. This is a highly selective approach, since it combines two orthogonal procedures [8] of isolation: organic solvent extraction and ion-exchange.…”
mentioning
confidence: 99%
“…NBS acylcarnitine profiling was performed as described by Chace et al (2003). Plasma acylcarnitine profiling was performed as described by Minkler et al (2005). In addition, keto-acylcarnitine profiling was performed by incubating 50 mL of plasma with 5 mL of MOX Reagent (Pierce, Rockford, IL, USA) containing 2% methoxyamineÁHCl in pyridine.…”
Section: Methodsmentioning
confidence: 99%
“…The mixture was left to stand at room temperature for 2 h to allow the formation of methoxime-derivatives of all keto-containing substances. Following this incubation, the samples were treated in the usual manner for the isolation and derivatization of acylcarnitines, which were analyzed as their butylester derivatives (Minkler et al 2005).…”
Section: Methodsmentioning
confidence: 99%